Pengaruh Jenis Sendi Lutut Kaki Prostetik Dan Postur Tubuh Statis Terhadap Aktivitas Otot Dan Rating of Percieved Discomfort (RPD) Pada Pengguna Kaki Prostetik - Dewati, Alifta Agdiana; Muslim, Khoirul (Journal of Research in Industrial Engineering and Management, 2024)
Differences in prosthetic leg design and mechanism affect lower limb muscle activity. Unbalanced muscle activity has the potential to reduce the function of physical mobility and change the balance point which has an impact on reducing performance, causing a decrease in the productivity of people with amputation disabilities. This study aims to determine the effect of awkward body posture and type of prosthetic foot on muscle activity in prosthetic foot users. This study used a within subject design with a total of six participants. Independent variables include body posture and type of prosthetic foot. Electromyography signal measurements on the biceps femoris (BF), gactrosnemius (GC), rectus femoris (RF), erector spinae (ES) muscles were performed to evaluate the level of muscle activity. Electromyography signals were processed with a 10-450Hz band-pass filter. ANOVA Repeated Measure obtained the results of awkward posture affecting muscle activity, especially in GC, BF, and ES muscles in the normal leg. In conclusion, the type of prosthetic leg does not affect muscle activity, but body posture has a significant effect on muscle activity although not in all muscles. This study can be used as advice to transfemoral amputation patients to use prosthetic feet that can reduce the risk of WMSDs so as to improve daily performance like normal individuals.